Serum Leptin and Adiponectin Levels and the Coronary Artery Disease in Patients Undergoing Angiography - Bagheri, Ahmad Reza; Molaei, Sedigheh; Parviz, Negar; Yoosefee, Sadegh (Shahroud Journal of Medical Sciences, 2025)
Background: It has been shown the adipokines, including leptin and adiponectin, have a prominent role in the pathogenesis of coronary artery disease (CAD). Nevertheless, conflicting results have been reported. The aim of the current study was to clarify the association of the leptin, adiponectin, and leptin to adiponectin (L/R) ratio with the severity of coronary atherosclerosis in an Iranian patient with CAD undergoing angiography.Methods: We evaluated leptin, adiponectin, and leptin/ adiponectin (L/A) ratio as predictors of CAD severity in 179 Iranian patients based on the severity of CAD. Participants were divided into four groups. Statistical analyses were performed using SPSS22 software, and significance was defined as P-value<0.05.Results: Among participants 78 persons (43.6%) were female. The mean (SD) age, BMI, serum leptin, adiponectin levels were 58.99 (10.07), 28.26 (4.11), and 1.55 (0.40), 8.48 (2.40) respectively. The angiographic evaluations of patients showed that 52 (29%) of participants had only one involved vessel, 29 (16%) had two involved vessels, 26 (15%) had three involved vessels, and 72 (40%) had mild vessel involved.Conclusions: Our analysis found no significant link between L/A ratio and CAD severity.